The Interventions to enhance the Well-being of Children at early education in China: The Mediating Moderating Approach - Ni limei; Kang Xi (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research effort depicts the well-being of children in China who have experienced devastating developments in their immediate environment and are indulged in negative emotions which result in negative psychological and behavioral consequences. The study focuses on the interventions taken into consideration in prior literature to address the problem of the ‘left-behind children’. The current research paper seeks to assess the well-being of children influenced by important factors that shape the behavior at early schooling. Tolerance, respect and moral identity are found to be crucial factors that influence individual behavioral outcomes; therefore, the current study empirically investigates the impact of these behavioral interventions. The study reports mixed results as two direct hypotheses’ i.e., moral identity to well-being and tolerance-respect to well-being are observed to be insignificant, however the remaining direct, moderating, and mediating relationship are found to be statistically significant. The implications, limitations and future directions of the current research study are highlighted in the concluding sections of the study.